2016
DOI: 10.1002/cta.2305
|View full text |Cite
|
Sign up to set email alerts
|

A switched‐capacitor skew‐tent map implementation for random number generation

Abstract: Piecewise linear one-dimensional maps have been proposed as the basis for low-power analog and mixedsignal true random number generators (TRNGs). Recent research has moved towards conceiving maps that operate robustly under the consideration of parameter variations. In this paper, we introduce an oscillator circuit mapping a low-complexity map known as the skew-tent. This oscillator is employed as the basis for a TRNG scheme. Simulation results in TSMC 0.18 m validate the chaotic oscillator and the randomness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Proposition 1. The error system described by (11) and (13) is asymptotically stable if there exists a matrix P = P T > 0 such that…”
Section: Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…Proposition 1. The error system described by (11) and (13) is asymptotically stable if there exists a matrix P = P T > 0 such that…”
Section: Complexitymentioning
confidence: 99%
“…A sufficient condition for the asymptotic stability of system (13) is that there exists a matrix P = P T > 0 such that…”
mentioning
confidence: 99%
“…Discrete maps have attracted significant attention in the study of dynamical systems [ 1 , 2 , 3 , 4 ]. Discrete maps appear in various disciplines including physiology, chemistry, physics, ecology, social sciences and engineering [ 3 , 5 , 6 , 7 ]. It has previously been observed that simple first-order nonlinear maps can generate complex dynamical behavior including chaos [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, some systems have the properties of amplitude control and offset boosting [ 1 , 2 , 3 , 4 ]. In this paper, we use a new three-dimensional (3D) chaotic system in random number generation and signal encryption, which are important engineering applications of chaotic systems [ 5 , 6 , 7 , 8 , 9 , 10 ]. To do this, an electronic design of the system is implemented as a real electronic circuit to generate random numbers.…”
Section: Introductionmentioning
confidence: 99%